The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1126/science.1230855
|View full text |Cite
|
Sign up to set email alerts
|

Outside the Pipeline: Reimagining Science Education for Nonscientists

Abstract: Educational policy increasingly emphasizes knowledge and skills for the preprofessional "science pipeline" rather than helping students use science in daily life. We synthesize research on public engagement with science to develop a research-based plan for cultivating competent outsiders: nonscientists who can access and make sense of science relevant to their lives. Schools should help students access and interpret the science they need in response to specific practical problems, judge the credibility of scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 22 publications
4
101
0
8
Order By: Relevance
“…This conclusion is supported by Feinstein et al (2013) who argued that policy makers of today focus on producing science-ready students. However, if the goal for school science is to be less alienating and bring about Bcompetent outsiders^ (Feinstein 2011), or to create an interest and engagement in more and diverse student groups, a greater balance is needed (Zacharia and Barton 2004).…”
Section: Aims and Goals Of School Sciencesupporting
confidence: 60%
See 3 more Smart Citations
“…This conclusion is supported by Feinstein et al (2013) who argued that policy makers of today focus on producing science-ready students. However, if the goal for school science is to be less alienating and bring about Bcompetent outsiders^ (Feinstein 2011), or to create an interest and engagement in more and diverse student groups, a greater balance is needed (Zacharia and Barton 2004).…”
Section: Aims and Goals Of School Sciencesupporting
confidence: 60%
“…Such school science has been discussed in terms of developing students' abilities to deal with uncertain knowledge and conflicting evidence through, among other things, being able to make judgements about trustworthiness and credibility and to use media as a source. In many cases, it is suggested that this should be done through authentic and context-rich activities (Allchin 2014;Feinstein et al 2013;Hodson and Wong 2014). The project described here takes a point of departure in science education research on NOS.…”
Section: Aims and Goals Of School Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…scientific literacy, myös science literacy) (European Commission, 2004;Feinstein, Allen, & Jenkins, 2013;Opetushallitus, 2014;Osborne, 2007;Osborne & Dillon, 2008). Suomeksi englanninkielinen termi scientific literacy kääntyy luonnontieteelliseksi lukutaidoksi, luonnontieteelliseksi sivistykseksi tai luonnontieteiden osaamiseksi (ks., esim.…”
Section: Johdantounclassified